Statistical analysis of abstentionism in the presidential elections of Costa Rica, 2014 - Araya Alpízar, Carlomagno (2015)
This paper statistically analyzes the electoral abstention by districts and provinces in the presidential elections of Costa Rica 2014. The author studies the importance of socioeconomic variables as the Social Development Index (IDS), with the aim of studying the factors that originate and represent a problem of legitimacy of the Costa Rican political system. It was found that voter abstention in the districts of Costa Rica is distributed unequally in relation to demographic and economic characteristics, is negatively correlated with the social development index, and is higher among people with lower average age; abstention´s frequency was higher in places where there is more economic dependency and is lower in urban areas; districts with low population density tend to have lower electoral participation . In addition, it was found that the Partido Acción Ciudadana had a positive effect in reducing absenteeism.